High ecomorphological diversity among Early Cretaceous frogs from a large subtropical wetland of Iberia - Gomez, Raul Orencio (2019)
Anurans are extremely diverse amphibians with a unique Bauplan, whose origin, early ecomorphological diversification, and adaptive significance remain elusive. Their early fossil record is improving at an accelerated pace worldwide, but its contribution to these issues is still wanting. Here we explore ecomorphological diversity among Early Cretaceous (Barremian) frogs that inhabited a large subtropical wetland from Iberia by inferring locomotor abilities with a phylogenetic flexible discriminant analysis on data from limb proportions, which strongly correlate with locomotion. The results show a remarkable diversity among these frogs when compared with the extant diversity from this region and from tropical and subtropical wetland assemblages worldwide, encompassing miniature to medium-size jumpers and dedicated swimmers with more extreme proportions than extant ‘archeobatrachians,’ but also more generalized jumping and/or swimming forms. This agrees with the inferred wetland paleoenvironment and the hypothesis regarding early frogs as small poor jumpers or swimmers that evolved their peculiar Bauplan in aquatic environments.